Pengaruh Kinerja Keuangan Terhadap Rate of Return (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di BEI Tahun 2014-2018 ) - Sefka Anggraini Putri; Reni Oktavia; Widya Rizki Eka Putri (Faculty of Economics and Business, 2020)
The purpose of this study was to examine the effect of financial performance on the rate of return. The indicators used to measure financial performance are return on investment, net profit margin, earnings per share, operating cash flow, economic value added. This study uses secondary data with a population of companies listed on the Indonesia Stock Exchange (BEI) 2014-2018. The method used to determine the sample using purposive sampling. Consists of 19 industrial mining companies with 56 samples. The analysis method used is multiple regression analysis. The results of hypothesis testing show that the Return on Investment (ROI) has no significant effect on the Rate of Return (ROR), Net Profit Margin (NPM) has significant effect on the Rate of Return (ROR), Earning Per Share (EPS) has no significant effect on the Rate of Return (ROR), Operating Cash Flow(OCF) has no significant effect on the Rate of Return (ROR), Economic Value Added (EVA) has no significant effect on the Rate of Return (ROR)